A numerical study of the effects of reformer gas composition on the combustion and emission characteristics of a natural gas/diesel RCCI engine enriched with reformer gas. (1st December 2017) - Rahnama, Pourya; Paykani, Amin; Bordbar, Vahid; Reitz, Rolf D.
Highlights: Shortened ignition delay and advanced CA50 were obtained with higher CO content. RI and PRR were increased significantly with increasing CO fraction in the syngas. By syngas enrichment, CO and NOx declined as the H2 in the mixture increased. High-H2 mixtures requires intake preheating more than ones with low-H2 content. Abstract: In natural gas/diesel Reactivity Controlled Compression Ignition (RCCI) engines, the large reactivity gradient between the two fuels is beneficial in achieving lower pressure rise rate and peak pressure values at high loads. However, by using natural gas, combustion efficiency and engine performance suffer at low loads due to its lower reactivity and higher ignition delay compared to gasoline. The use of reformer gas (containing H2 and CO), which can be produced onboard by a catalytic fuel reformer integrated within the exhaust pipe, as an additive can improve the combustion process of the engine at low loads since it enhances burning rate and compensates the low reactivity of natural gas. The objective of the present study is to investigate the effect of reformer gas (syngas) composition on the performance and exhaust emissions properties of a natural gas/diesel RCCI engine at low loads numerically, when 3% of intake air is volumetrically replaced by reformer gas. Shortened ignition delay and combustion duration, advanced combustion phasing (CA50), and increased peak pressure rise rate, ringing intensity, and lower combustion efficiency were obtained by the mixture with higher CO content. The results indicated that reformer gas addition could enhance the combustion efficiency and decrease CO emission, however, the mixture with higher hydrogen content requires intake charge preheating more than that with lower hydrogen content and mixture with higher CO content is more sensitive to intake temperature.